La sociedad capitalista como negación del ocio: historia de una paradoja actual - Royo Hernández, Simón (Logos. Anales del Seminario de Metafísica, 2002)
The realm of freedom in materialist tradition depends on the liberation of work through the reappropriation of the means and conditions of life. The appropriation of technology is especially important. Indeed, it is a means to provide a leisurethat has nothing to do with laziness and indulgence and has much to do with activity in freedom. Since capitalism is based on the denial of leisure, it is all the more necessary to obtain leisure now that we live in a society where there never had been so many chances of liberation from work and, at the same time, people never had worked so much.